PO31 Study of inhibitory potential of some species of the genus Piper against Pancreatic Lipase - Gomez Alvarado, Wendy Lorena; Ladino Patiño, Oscar Javier; Prieto Rodriguez, Juliet Angélica (Revista Productos Naturales, 2025)
Pancreatic lipase (PL) is a key enzyme in lipid digestion and a widely studied therapeutic target for obesity treatment. Inhibition of PL reduces fat absorption and promotes weight loss; however, available drugs have limitations related to adverse effects and variable efficacy [1]. This situation has driven the search for safer natural alternatives, among which plants of the Piper genus (Piperaceae) known for their diversity of secondary metabolites, some of which can inhibit digestive enzymes such as PL [2].
Keywords: Piper; enzymatic inhibition; pancreatic lipase; obesity; chromenes; chromans